Genetic ablation of TASK-1 (tandem of P domains in a weak inward rectifying K+ channel-related acid-sensitive K+ channel-1) (K2P3.1) K+ channels suppresses atrial fibrillation and prevents electrical remodeling - Schmidt, Constanze; Wiedmann, Felix Tobias; El-Battrawy, Ibrahim; Lan, Huan; Szabó, Gábor; Lang, Siegfried; Rapti, Kleopatra; Ratte, Antonius; Karck, Matthias; Akın, Ibrahim; Borggrefe, Martin; Zhou, Xiao-Bo; et al. (Circulation. Arrhythmia and electrophysiology, 2019)
Background:Despite an increasing understanding of atrial fibrillation (AF) pathophysiology, translation into mechanism-based treatment options is lacking. In atrial cardiomyocytes of patients with chronic AF, expression, and function of tandem of P domains in a weak inward rectifying TASK-1 (K+ channel-related acid-sensitive K+ channel-1) (K2P3.1) atrial-specific 2-pore domain potassium channels is enhanced, resulting in action potential duration shortening. TASK-1 channel inhibition prevents action potential duration shortening to maintain values observed among sinus rhythm subjects. The present preclinical study used a porcine AF model to evaluate the antiarrhythmic efficacy of TASK-1 inhibition by adeno-associated viral anti-TASK-1-siRNA (small interfering RNA) gene transfer.Methods:AF was induced in domestic pigs by atrial burst stimulation via implanted pacemakers. Adeno-associated viral vectors carrying anti-TASK-1-siRNA were injected into both atria to suppress TASK-1 channel expression. After the 14-day follow-up period, porcine cardiomyocytes were isolated from right and left atrium, followed by electrophysiological and molecular characterization.Results:AF was associated with increased TASK-1 transcript, protein and ion current levels leading to shortened action potential duration in atrial cardiomyocytes compared to sinus rhythm controls, similar to previous findings in humans. Anti-TASK-1 adeno-associated viral application significantly reduced AF burden in comparison to untreated AF pigs. Antiarrhythmic effects of anti-TASK-1-siRNA were associated with reduction of TASK-1 currents and prolongation of action potential durations in atrial cardiomyocytes to sinus rhythm values.ConclusionsAdeno-associated viral-based anti-TASK-1 gene therapy suppressed AF and corrected cellular electrophysiological remodeling in a porcine model of AF. Suppression of AF through selective reduction of TASK-1 currents represents a new option for antiarrhythmic therapy.
Gesehen am 05.12.2019